Quality in Supply Chain Encroachment - Ha, Albert; Long, Xiaoyang; Nasiry, Javad (Manufacturing and Service Operations Management, 2016)
We study a supply chain with manufacturer encroachment in which product quality is endogenous and customers have heterogeneous preferences for quality. It is known that, when quality is exogenous, encroachment could make the retailer better off. Yet, when quality is endogenous and the manufacturer has enough flexibility in adjusting quality, we find that encroachment always makes the retailer worse off in a large variety of scenarios. We also establish that, while a higher manufacturer’s cost of quality hurts the retailer in absence of encroachment, it could benefit the retailer with encroachment. In addition, we show that a manufacturer offering differentiated products through two channels prefers to sell its high-quality product through the direct channel. Contrary to conventional wisdom, quality differentiation does not always benefit either manufacturer or retailer. Our results may explain why, despite extant theoretical predictions, retailers almost always resent encroachment. These findings also suggest that firms must be cautious when adopting quality differentiation as a strategy to ease channel conflict caused by encroachment.